Glycyrrhizin modulates ER stress-induced UPR and concomitant mitochondrial dysfunction and activation of NF-κB in alcohol and cerulein-induced pancreatitis in rats - Sarmishta Srikantam, Geetha Arumugam (Journal of Applied Pharmaceutical Science, 2021)
Chronic pancreatitis (CP), a long-lasting pancreatic inflammatory illness, results predominantly from prolonged alcohol abuse. No standardized treatment exists so far. This investigation studies the effect of glycyrrhizin (GZ) on ethanol (EtOH) and cerulein (Cer)-induced pathology in the pancreas of male albino Wistar rats. Endoplasmic reticulum (ER) stress, mitochondrial damage, and activation of nuclear factor-κB (NF-κB) are the important pathomechanisms of CP. Rats were sorted as follows: Group 1 (control) and group 2 (GZ control) were given normal diet for the total period of 5 weeks, whereas group 3 (EtOH + Cer) and group 4 (EtOH +Cer+ GZ) were given alcoholic diet (0%–36%) for 4 weeks and Cer (20 μg/kg of body weight, IP) three times a week for the last 3 weeks to induce CP. Group 2 and group 4 rats were also given GZ (10 mg/kg of body weight, oral) from third week. GZ co-administration modulated ER stress by downregulating mRNA expression of unfolded protein response components like activating transcription factor 4, 78 kDa glucose-regulated protein (GRP78), CCAAT-enhancer-binding protein homologous protein (CHOP), X-box binding protein 1 and the inflammatory mediator, NF-κB. In addition, GZ ameliorated cellular oxidative stress. Measurements of calcium, complex-1 activity, and oxidative stress [including 4-hydroxynonenal (4-HNE)] in mitochondria substantiated the protective effect of GZ against mitochondrial dysfunction. Applying spearman’s rank correlation (rs), a significant positive correlation between GRP78 versus 4-HNE (p < 0.05) and CHOP versus mitochondrial calcium (p = 0.00) was proved, which could indicate that ER stress and mitochondrial dysfunction act in concert to cause the pathobiology in CP. It can be concluded that GZ exhibits pancreato-protective effect against CP likely by targeting ER stress, NF-κB signaling, and by maintaining functional mitochondria.
Keywords: Pancreatitis, ER stress, mitochondrial oxidative stress, complex-1 impairment, calcium overload, glycyrrhizin.